Haremeyn, Şam, Cidde, Habeş, Yemen, Hindistan ve Mısır ile ilgili bir takrir - (:unkn) unknown (My University, 2014)
Burada değerlendirdiğimiz ve 1525 sonları ile 1526 başlarında kaleme alındığı- nı tahmin ettiğimiz takrir, XVI. yüzyılın ilk çeyreğine dair önemli kaynaklardandır. Takriri kimin yazdığı kesin olarak belli değildir. Takrir Mekke, Medine, Şam, Zebid, Yemen, Habeş, Cidde, Mısır, Hindistan, Gucerat ahvali ve Portekizin Hindistan’daki yayılması hakkında önemli bilgiler ihtiva eder. Makalemizde, bugüne kadar dikkatleri çekmemiş olan bu kaynağın müellifini, hangi tarihte yazıldığını ve mezkûr bölgelere dair ne gibi bilgiler içerdiğini ele aldık.

Report (takrir) that we have discussed here and assumed that it was written at the end of 1525 and at the beginning of 1526 is one of the important sources about the first quarter of the XVI. century. It isn’t certainly known who has written the report. The report includes important information about condition of Mecca, Medina, Damascus, Zabid, Yemen, Ethiopia, Jeddah, Egypt, India, Gujarat and about Portugal’s invasion of India. In our study we discussed the writer of this source who hasn’t attracted attention hitherto, when it was written and what kind of information it includes about the said areas.
A report on Haremeyn (Mecca, Medina), Damascus, Jeddah, Ethiopia, Yemen, India and Egypt
Keywords: Arkeoloji; Sanat; Tarih